The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1891/2168-6653.30.3.276
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Vocational Rehabilitation Engagement Scale When Used With People With Mental Illness in Clubhouse Settings

Abstract: Purpose:The purpose of this study was to validate the Vocational Rehabilitation Engagement Scale (VRES) for use in the Clubhouse Model of Psychosocial Rehabilitation.Method:There were 124 individuals with serious mental illness recruited from 8 Clubhouse programs in Hawaii. Measurement structure of the VRES was evaluated using exploratory factor analysis.Results:Exploratory factor analysis of the Clubhouse version of the VRES yielded 2 reliable factors (cognitive-affective engagement and behavioral engagement)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Each item is rated on a 5-point scale, ranging from strongly disagree (1) to strongly agree (5). Using the VRES with clients with mental illness in clubhouse settings, Fitzgerald et al (2016) reported an internal consistency reliability coefficient (Cronbach's alpha) of .86. The Cronbach's alpha for the VRES in this study was .95.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each item is rated on a 5-point scale, ranging from strongly disagree (1) to strongly agree (5). Using the VRES with clients with mental illness in clubhouse settings, Fitzgerald et al (2016) reported an internal consistency reliability coefficient (Cronbach's alpha) of .86. The Cronbach's alpha for the VRES in this study was .95.…”
Section: Methodsmentioning
confidence: 99%
“…Autonomy. The Behavioral Regulation in Work Questionnaire (BRWQ) was adapted from the Behavioral Regulation in Exercise Questionnaire-2 (BREQ-2; Markland & Tobin, 2004) by Fitzgerald et al (2016) to assess controlled motivation and autonomous motivation to obtain and retain employment. The BRWQ-Brief extracts two identified regulation items (e.g., "I want to work because I value the social and financial benefits of work") and two intrinsic regulation items (e.g., "I want to work because it is fun") to form a four-item Autonomous Work Motivation measure.…”
Section: Set/sdt Predictorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Vocational Self-Efficacy Scale (VSES; Fitzgerald et al, 2016) was used to assess participants vocational self-efficacy. The VSES is an adaptation of the Life Skills Inventory (LSI; Chan et al, 2003) that evaluated the life essential skills for assertive community living and work.…”
Section: Vocational Self-efficacy Scale (Vses)mentioning
confidence: 99%